Pattern of Pulmonary Dysfunctions in Craniovertebral Junction Anomaly and Its Persistence after Rigid Occipitocervical Fixation - Shaam Bodeliwala; Vikas Nagar; Hukum Singh; Daljit Singh; Anita Jagetia; Sharad Pandey; Rajesh Ruttala; Pankaj Kumar (Indian Journal of Neurosurgery)
Introduction Despite a significant advancement in operative techniques of occipitocervical fixation, there is a poor postoperative patient outcome. This can be attributed to restrictive lung pattern in craniovertebral junction anomalies (CVJAs) patients resulting from repeated trauma to cervicomedullary junction by the pincer action of the bony anomalies and compression of the brainstem. We evaluate the changes in pulmonary function tests (PFTs) following rigid occipitocervical fixation in CVJA. Methods PFTs of 20 CVJA patients were measured pre and postoperatively using spirometry. Measurements included forced vital capacity (FVC), forced expiratory volume in one second (FEV1), maximum forced mid-expiratory flow rate (FEF25–75%), and ratio of FEV1 and FVC (FEV1%). The parameters were compared with the predicted normal values based on their age and sex. PFTs were repeated on the seventh postoperative day. McCormick grading was used to assess neurological function. Results  The values of PFTs in the preoperative period were significantly lower than predicted normal values. The mean values of FVC, FEV1, FEF25–75% were 72, 68, and 71% of their mean predicted values, with FEV1% in the range of 70 to 95% with a mean of 81.4%. Postoperatively there was further significant reduction in the mean values of FVC, FEV1, FEF25–75%, and FEV1% compared with the preoperative values. There was neurological improvement in McCormick grades of patients postoperatively (from grade III and IV to grade II). Conclusion A significant restrictive lung disease is present in patients of CVJA, even though not clinically apparent, and it persists in the early postoperative period. However, a long-term follow-up is required to assess whether pulmonary function parameters improve subsequently.